2008
DOI: 10.1152/ajpregu.00186.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium manipulation during critical periods in development sensitize adult offspring to amphetamines

Abstract: McBride SM, Culver B, Flynn FW. Dietary sodium manipulation during critical periods in development sensitize adult offspring to amphetamines. Am J Physiol Regul Integr Comp Physiol 295: R899 -R905, 2008. First published July 9, 2008 doi:10.1152/ajpregu.00186.2008This study examined critical periods in development to determine when offspring were most susceptible to dietary sodium manipulation leading to amphetamine sensitization. Wistar dams (n ϭ 6 -8/group) were fed chow containing low (0.12% NaCl; LN), norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The primary aim of our study was to expand upon previous work by our colleagues that showed perinatal high‐salt exposure facilitated physiological adaptations to stress (McBride et al, ). In our structural analysis of weanling and adult rats, we observed an increase in spine density in the NAc‐Sh (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The primary aim of our study was to expand upon previous work by our colleagues that showed perinatal high‐salt exposure facilitated physiological adaptations to stress (McBride et al, ). In our structural analysis of weanling and adult rats, we observed an increase in spine density in the NAc‐Sh (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…B). This was curious given the previous reports that early high‐salt exposure increases the locomotor response to amphetamine (McBride et al, ) and that sodium appetite and cocaine‐induced locomotor behavior cross‐sensitize (Acerbo and Johnson, ). The CPP model however assesses a preference for drug‐associated environments rather than the mere physiological response to a drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Exposure to excess salt during early developmental periods may cause long-term physiological changes in later life in rats. 10 Following in utero exposure to high salt (HS), the offspring showed a suppressed renin-angiotensin system (RAS), indicating HS diet during pregnancy may reprogram RAS. 11,12 These may produce offspring with maladaptive phenotypes in a predicted adult life.…”
Section: Introductionmentioning
confidence: 99%